Microbial communities of wastewater in the Canadian Arctic - Gromala, Monica (University of Waterloo, 2019)
Wastewater management in the Canadian Arctic is challenging due to the extreme climate and lack of conventional treatment system infrastructure. To resolve these issues, most Northern communities use waste stabilization ponds (WSPs) as their sole form of wastewater management. In this type of system, wastewater is collected directly from buildings year-round and is transported to the WSP where it is discharged directly into the environment. For approximately nine months of the year, the wastewater remains frozen due to sub-zero temperatures. As the temperature increases in the spring, ice begins to melt, allowing the wastewater to thaw and flow into downstream lakes. Increased sunlight and increased water temperatures stimulate microorganisms to naturally breakdown the various components of the wastewater and reduce concentrations of macronutrients, such as nitrogen and phosphorus. The two to three months during which temperatures remain above zero are collectively referred to as the treatment season as the majority of aerobic and anaerobic degradation occurs during this time. Currently, the microbial communities of Arctic WSPs are not well understood. Identifying the major microorganisms in the microbial communities of these WSPs is important for understanding whether the wastewater treatment system is effective in the removal of wastewater contaminants from effluent water flowing into downstream lakes. This research aims to characterize the microbial community and identify wastewater indicator organisms of three Arctic WSPs in Baker Lake, Cambridge Bay, and Kugluktuk in Nunavut, Canada, with a focus on the Baker Lake WSP and the downstream lake system. In Baker Lake, wastewater is discharged into a lagoon, where water is able to flow into downstream lakes before ultimately discharging into Baker Lake. Several sites across this entire system, as well as three reference sites were sampled and analyzed to produce baseline taxonomic profiles. This was achieved through 16S rRNA gene and metagenome sequencing, and ...